2010
DOI: 10.1021/pr100707t
|View full text |Cite
|
Sign up to set email alerts
|

Chips from Chips: Application to the Study of Antibody Responses to Methylated Proteins

Abstract: Peptide microarrays are useful tools for the characterization of humoral responses against peptide antigens. The study of post-translational modifications requires the printing of appropriately modified peptides, whose synthesis can be time-consuming and expensive. We describe here a method named "chips from chips", which allows probing the presence of antibodies directed toward modified peptide antigens starting from unmodified peptide microarrays. The chip from chip concept is based on the modification of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…Inspired by the hydrophilic patterned beetles’ backs, many wettability-patterned surfaces have been produced on various inorganic and organic materials such as metals, oxides, and polymers [78,79,80,81,82,83,84,85,86,87,88,89]. Recently, Seo et al demonstrated hydrophilic-patterned superhydrophobic Si NW arrays to guide water droplets [77].…”
Section: Design and Fabrication Of Bio-inspired Extreme Wetting Sumentioning
confidence: 99%
“…Inspired by the hydrophilic patterned beetles’ backs, many wettability-patterned surfaces have been produced on various inorganic and organic materials such as metals, oxides, and polymers [78,79,80,81,82,83,84,85,86,87,88,89]. Recently, Seo et al demonstrated hydrophilic-patterned superhydrophobic Si NW arrays to guide water droplets [77].…”
Section: Design and Fabrication Of Bio-inspired Extreme Wetting Sumentioning
confidence: 99%
“…This combination has permitted classical basic operations such as displacement of sample droplet, precise sample distribution and subsequent rinsing step prior to MS detection [32]. The same surfaces have also been used for the detection of methylation level of peptides, proving that these silicon nanowire array-based surfaces have a great potential in proteomic analysis [33]. However, such peptide sampling is not sufficiently representative of the sequence diversity that is encountered in proteomics, which justifies broadening the scope of the research to the analyses of numerous proteolytic peptides and mixtures of proteolytic peptides including multiple tryptic digests.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, nanostructured silicon substrates, [8][9][10][11][12][13][14][15] nanostructured diamond, 16,17 germanium nanodots, 18 gold 19-21 and silver nanoparticles, 22,23 carbon nanotubes, 24,25 platinum nanoflowers, 26 zinc oxide (ZnO) nanowires, 27 and porous alumina 28 have successfully been used as highly efficient matrices in SALDI-MS. Indeed, nanostructured silicon substrates, [8][9][10][11][12][13][14][15] nanostructured diamond, 16,17 germanium nanodots, 18 gold 19-21 and silver nanoparticles, 22,23 carbon nanotubes, 24,25 platinum nanoflowers, 26 zinc oxide (ZnO) nanowires, 27 and porous alumina 28 have successfully been used as highly efficient matrices in SALDI-MS.…”
Section: Introductionmentioning
confidence: 99%